A pothole-filling strategy for selective targeting of rCUG-repeats associated with myotonic dystrophy type 1 - J. Dinithi R. Perera; Shivaji A. Thadke; Savani W. Thrikawala; Isha Dhami; V. M. Hridya; Arnab Mukherjee; Ananya Paul; W. David Wilson; Keith W. R. Tan; Nicholas Z. W. Chan; Anh Tuân Phan; Danith H. Ly (Proceedings of the National Academy of Sciences, 2026)
We present an alternative approach to conventional small-molecule and antisense strategies for selectively targeting expanded CUG-RNA repeats associated with Myotonic Dystrophy type 1. Our alternatively designed nucleic acid ligands uniquely integrate advantageous features from both existing methods: They are compact (only three units in length), structurally resembling small molecules, yet recognize RNA targets through directional hydrogen-bonding similar to antisense oligonucleotides. Notably, these ligands exhibit greater specificity and selectivity than either approach alone. This enhanced specificity results from their bifacial recognition mechanism, wherein mismatches on one binding interface are reciprocally mirrored on the complementary face. Additionally, their short length significantly amplifies specificity, as even a single mismatch substantially reduces the overall binding free energy, effectively minimizing off-target interactions. Unlike conventional oligonucleotides, these ligands avoid binding single-stranded RNA and only recognize defined hairpin motifs via a “pothole-filling” mechanism. This method amplifies recognition specificity and selectivity, circumventing the thermodynamic penalties associated with RNA unfolding. This proof-of-concept study thus lays a foundation for developing versatile nucleic acid ligands capable of selectively targeting not only pathogenic CUG-RNA repeats in Myotonic Dystrophy type 1 but also other disease-associated triplet-repeat expansions prevalent in various neuromuscular disorders.